Hubungan dukungan suami dan pengetahuan ibu terhadap pemberian asi eksklusif di Puskesmas Pahandut Kota Palangka Raya - Napitupulu, Lisha Pebriani; Widiarti, Astri; Patricia, Tisha (Barigas: Jurnal Riset Mahasiswa, 2023)
Breast milk contain the nutrition needed for the growth and development of baby. Exclusive breastfeeding is the basic capital for the formation of quality humans, but the percentage of exclusive breastfeeding in the world, in the city of Palangka Raya, and in the health center of pahandut is stil low. The World Health Organization (WHO) report that in 2016 the percentage of exclusive breastfeeding is 38%. Exclusive breastfeeding in the city of Palangka Raya in 2021 around 33.17%, and in the Pahandut health center there is only 7.45%. This study was to know the relationship of husband support and mother’s knowledge with exclusive breastfeeding in puskesmas Pahandut. This study used an analytical observational method with cross-sectional. The sampling technique was carried out purposive sampling. Amount of 78 samples in accordance with criteria of inclusion were analyzed using chi square statistical test. This study was conducted in Pahandut health center, from July to September 2022. The sample in this study were mothers who had babies aged 6-12 months and lived in the work area of Pahandut health center. There was relationship between husband's support for exclusive breastfeeding with p-value 0,007 and there was relationship between mother's knowledge with exclusive breastfeeding with p-value 0,001.